Assessing and managing the factors contributing to radio listeners' choice a study of cats fm / Rosemiyati Mohd. Nawawi ... [et al.]. - Mohd. Nawawi, Rosemiyati; Bujang, Julia; Annuar, Noraslin (2010)
The survival of a radio station depends on the listeners' tuning into its radio programs hence understanding the listeners' preferences will contribute to listeners' acceptance of CATS FM. The objectives of the study were to ascertain listeners' overall perception toward CATS FM, identify factors leading to radio listeners' choice of CATS FM, determine the most important factor(s)/ preferences and to propose strategies on how CATS FM could improve the listeners' perception. The study employed both descriptive and empirical methods. A structured questionnaire was developed based on established instruments for the industry and also through responses gathered from the focus groups. The distribution of questionnaires covered listeners in all seven divisions of Sarawak where CATS FM is transmitted as well as CATS FM personnel and experts of the field.